How Digital Marketing impacts in Advertising Agency over regular marketing: A perspective on SkyWalk Solutions Advertising Agency - Iqbal, MD Saif (BRAC University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.